Institutional Ownership, Independent Board of Commissioners on Company Value and Capital Structure as Moderating Variables - Padila Padila; Yuliusman Yuliusman; Muhammad Ridwan (International Journal of Economics, Commerce, and Management, 2025)
This study aims 1) to determine the effect of Institutional Ownership, independent board of commissioners and capital structure on Firm Value. 2) To determine the effect of Capital Structure in moderating Institutional Ownership and independent board of commissioners on Firm Value. The research method uses quantitative descriptive analysis with secondary data types. The analysis tool used in this study was carried out using the PLS (Partial Least Squares) approach with outer model and inner model measurement models using Smart PLS 3 software. The results of the study showed that Institutional Ownership had an effect on firm value. While the independent board of commissioners and capital structure did not affect firm value. Capital structure did not moderate the effect of institutional ownership and independent board of commissioners on firm value.